De vele kanten van leesbegrip Literatuurstudie naar onderwijs in begrijpend lezen in opdracht van het Nationaal Regieorgaan Onderwijsonderzoek en de Inspectie van het Onderwijs - Houtveen, A.A.M (Erasmus University Rotterdam, 2019)
This study provides an overview of what is known from research about effective education in reading comprehension. The report forms the framework for a survey of the state of the art of reading comprehension at the end of primary education that will be conducted in 2021.